Jamaica. 2014-2018 Medium Term Plan - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
Presents the country strategy for the period 201-2018, taking into account the context analysis of the agricultural sector, the vision and trends in agriculture and rural life, the challenges and opportunities, the needs and requests for technical cooperation and capacity development , as well as the instruments of action.